INTERNALISASI NILAI-NILAI SPIRITUAL DALAM PEMBENTUKAN KARAKTER SISWA DI SMP ISLAM AL-MAARIF 01 SINGOSARI - Nazili Masruri; Nur Hasan; Muhammad Fahmi Hidayatullah (VICRATINA, 2021)
The development of science and technology today leaves several issues that need attention. It is undeniable that modern society has succeeded in developing science and technology to become an alternative to solving problems of daily life, but in other conditions, advanced science and technology is less able to cultivate noble morality. In overcoming this problem, Smp Islam Al-ma'arif 01 singosari carries out the process of internalizing spiritual values the formation of a student's personality through religious activities. This study uses a qualitative phenomenology-based approach in case study type studies. The results of this study show that the internalization process carried out through religious activities makes good changes to develop mental values students. This is supported by the school's support factors, such as quality familiarity. while the obstacles in the process of internalizing spiritual values are the diverse backgrounds of students. Kata Kunci: Internalisation, Spiritual Values, Character Building